Innovation systems in regions of Europe: A comparative perspective - Franz Todtling (European Regional Science Association (ERSA), 1998)
The understanding of the innovation process has changed considerably in the past years. Models have shifted from linear and firm based conceptions towards interdependent and systemic approaches. Both national and regional innovation systems have been discussed in recent literature. The present paper investigates on the basis of data for eight European regions, collected in the course of a European project, to which extent companies engage into networks in their innovation process. Also, the types of partners, their respective locations (regional, national, European) as well as differences between the regions are explored. First results show, that for many firms innovation is still a rather internal process. Reliance on internal competence, lack of trust to other firms and fear of losing economic benefits to others are among the reasons. Nevertheless, for another group of companies networks are much more relevant. They draw on ideas, know-how and complementary assets from customers, suppliers, consultants, universities, funding and training institutions. With regard to the spatial reach of networks, we find considerable differences between company types and regions, however.
Keywords: 330